Adverse pregnancy outcomes and complications of tuberculosis in pregnant women - Su, Yinfeng; Kong, Xingxing; Chen, Zhanpeng; Wang, Xiaomin; Lu, Shuihua (Frontiers in Cellular and Infection Microbiology, 2025)
Tuberculosis in pregnancy is a series of diseases caused by Mycobacterium tuberculosis (Mtb). Exact global incidence rates are difficult to obtain and are expected to be similar to those in the general population, with potentially higher rates in developing countries. Tuberculosis in pregnancy is associated with adverse reactions in both mother and fetus, but the mechanism is not fully understood. Although many studies have explored the impact of tuberculosis on pregnancy outcomes and complications, there are still relatively few summary articles on it. This review aims to briefly summarize the adverse pregnancy outcomes and related complications of pregnant women with tuberculosis. Studies have shown that the risk of death for mothers with tuberculosis increases, and these mothers are more likely to have complications such as gestational hypertension, rupture of pulmonary bullae, postpartum hemorrhage, sepsis, anemia, placental chorioamnionitis, and gestational diabetes. In addition, tuberculosis infection during pregnancy also increases the risk of vertical transmission of Human Immunodeficiency Virus (HIV), leading to an increased chance of fetal infection with Mtb and an increased possibility of congenital tuberculosis in newborns. Besides, fetuses born to mothers with tuberculosis are at an increased risk of congenital malformations, intrauterine growth restriction, low birth weight, premature birth, miscarriage, and stillbirth.